Two faces of the feminist dystopia in the United Kingdom: Sophie Mackintosh and Rebecca Ley (Altre Modernità, 2022)
Two faces of the feminist dystopia in the United Kingdom: Sophie Mackintosh and Rebecca LeyA conversation with Sophie Mackintosh and Rebecca Leyby Marta Olivi